Representation Of The Concept Of Time In The Linguistic Consciousness - Sametova, Fauziya; Chakyroglu, Altynshash Kurmanali; Smanova, Bakhytgul; Sarymbetova, Almakul; Seidikenova, Almash (Opción, 2019)
The article deals with the representation of time in the linguistic consciousness of the representatives of different lingua cultures via comparative qualitative research methods. The paper also examines the results of the free association experiment, the aim of which was to determine the perception of the concept of time. As a result of the data of the associative experiment, the value-based and figurative components of the concept time were revealed. In conclusion, the associative field’s analysis provides an opportunity to access directly the ways of storing images of linguistic consciousness of representatives of different linguistic cultures.